2007
DOI: 10.1007/s00421-007-0562-0
|View full text |Cite
|
Sign up to set email alerts
|

Is the magnitude of acute post-exercise hypotension mediated by exercise intensity or total work done?

Abstract: The purpose of this study was to investigate the effects of exercise intensity on the magnitude of acute post-exercise hypotension while controlling for total work done over the exercise bout. Seven normotensive physically active males aged 28 +/- 6 years (mean +/- SD) completed four experimental trials, a no exercise control, 30 min of semi-recumbent cycling at 70% VO2peak (INT), cycling for 30 min at 40% VO2peak (SMOD) and cycling at 40% VO2peak for a time which corresponded to the same total work done as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
75
3
42

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(129 citation statements)
references
References 26 publications
(33 reference statements)
8
75
3
42
Order By: Relevance
“…However, other studies have detected post-exercise BP reductions in this subgroup. 3,5,25,26 Consistent with the present study, other investigators have reported that BP reductions are greater in hypertensive than in NT persons. 27,28 Regarding the effect of exercise duration and intensity on BP reduction, the present results were similar to those reported in other studies conducted with elderly individuals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, other studies have detected post-exercise BP reductions in this subgroup. 3,5,25,26 Consistent with the present study, other investigators have reported that BP reductions are greater in hypertensive than in NT persons. 27,28 Regarding the effect of exercise duration and intensity on BP reduction, the present results were similar to those reported in other studies conducted with elderly individuals.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is still no consensus as to how these variables interact with hypertension classifications according to the Guidelines of the European Society of Hypertension. 3,5 We emphasize the importance of an activity diary as a complementary method for subjectively determining sleep periods, which is essential for documenting the events occurring during the activity-recording period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseado na classificação segundo o %FC max , o bolero foi realizado em intensidade moderada e o samba em intensidade vigorosa, uma vez que a FC atingida durante a sessão de bolero foi entre 64 -76 %FC max (ritmo moderado) e durante a sessão de samba entre 77 -95 %FC max (ritmo vigoroso), mesmo considerando os picos de FC durante as danças. Várias pesquisas já investigaram o efeito da intensidade na magnitude e duração das respostas cardiovasculares pós-exercício aeróbio [14][15][16][17][18][19] , entretanto, o efeito da intensidade na hipotensão pós-exercício ainda não está clara. Por exemplo, enquanto Jones et al 19 16 demonstram que exercício de alta intensidade promove maior queda na PA pós-exercício.…”
Section: Discussionunclassified
“…Várias pesquisas já investigaram o efeito da intensidade na magnitude e duração das respostas cardiovasculares pós-exercício aeróbio [14][15][16][17][18][19] , entretanto, o efeito da intensidade na hipotensão pós-exercício ainda não está clara. Por exemplo, enquanto Jones et al 19 16 demonstram que exercício de alta intensidade promove maior queda na PA pós-exercício. Assim, apesar de existirem evidências de que quanto maior a intensidade de exercício maior será a magnitude e duração da hipotensão pós-exercício, as recomendações ainda são de que maior trabalho total (que pode ser atingido com maior intensidade ou maior volume) está associado com maiores benefícios para a saúde, quando realizado de forma crônica 6,13 .…”
Section: Discussionunclassified